واقع استخدام مديري مدارس الحلقة الثالثة بإمارة أبوظبي لمدخل الإدارة الالكترونية و علاقته بتحسين أدائهم - Ali Husain Ali Saqr Alhosani; Kirembwe Rashid Abdul Hamed; Nurkhamimi Zainuddin (Penerbit USIM, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.